Aktivitas Antibakteri Staphyloccocos aureus dan Salmonella thypi Ekstrak Metanol Anggur Laut (Caulerpa racemosa) - Sri Hainil; Suci Fitriani Sammulia; Adella Adella (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Sea Grape is one type of marine plant that produces active compounds that have the potential as medicinal ingredients that have antibacterial properties to inhibit the growth of bacteria that cause infectious diseases. This study aims to determine the antibacterial activity of sea grapes from Kampung Terih, Nongsa Beach, Riau Islands. The bacterial test used was Staphylococcus aureus and Salmonella typhi. Antibacterial activity testing using the disc paper diffusion method was carried out by measuring the inhibition zone around the disc paper, using a concentration variant of 25%, 75%, 100%. The results showed that sea grape extract was able to inhibit the growth of Staphylococcus aureus bacteria by forming an average diameter at each concentration of 8.4 mm (medium inhibition); 9.1 mm (medium resistance); 15.7 mm (strong resistance); then Salmonella typhi bacteria formed an average diameter at each concentration of 8.3 mm (medium inhibition); 9.3 mm (medium inhibition); 19.9 mm (strong resistance). Sea grape extract has strong potential in inhibiting bacterial growth.